2001
DOI: 10.1007/s002640100250
|View full text |Cite
|
Sign up to set email alerts
|

Reinfusion of drained blood as an alternative to homologous blood transfusion after total knee replacement

Abstract: In patients undergoing total knee replacement we carried out a longitudinal cohort study to determine the efficacy and safety of a postoperative autologous blood reinfusion system, as an alternative to homologous, banked blood transfusions. Fifty patients received reinfusion of unwashed, filtered, shed blood, supplemented with banked blood transfusions as required. A control group of 50 patients in whom standard suction drains were used received homologous blood transfusions as required. In the study group, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 8 publications
3
30
0
1
Order By: Relevance
“…Our results are in agreement with published series (Table 2). Our results are comparable to those of Sinha et al [15], who showed that homologous blood use can be reduced with the use of autologous transfusion following TKR. They reported an 80% drop in the rate of homolgous blood transfusion with the use of ABT.…”
Section: Discussionsupporting
confidence: 81%
“…Our results are in agreement with published series (Table 2). Our results are comparable to those of Sinha et al [15], who showed that homologous blood use can be reduced with the use of autologous transfusion following TKR. They reported an 80% drop in the rate of homolgous blood transfusion with the use of ABT.…”
Section: Discussionsupporting
confidence: 81%
“…Different studies [6,7,18,19,23,24] have reported a decreased blood transfusion requirement using a postoperative autologous blood reinfusion system. Peter et al [19] reported a blood transfusion requirement in the study group without an autologous blood reinfusion system in 67 of 93 patients (72%) which dropped to 19% using a reinfusion system.…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons use a reinfusion system of autologous blood [19,23] and others use closed suction drainage [11] following elective knee arthroplasty. Theoretically, a wound drain should minimise postoperative haematoma and all of the complications with which it is associated [4].…”
Section: Introductionmentioning
confidence: 99%
“…transfusions include autologous blood transfusion [10,34,37], postoperative blood salvage [1,9,16,20,21,34,52], use of a femoral intramedullary plug [43], hypotensive anesthesia [30], cryotherapy and Jones bandage [18], use of fibrin tissue adhesive [33,58], drain clamping [41,42,45,46,48,51,54,59], and administration of tranexamic acid [6-8, 19, 23, 24, 27, 28, 35, 39, 53, 55].…”
mentioning
confidence: 99%